The Implementation of Smart Iron as Supporting Technology for Blind Junior High School Students in Ironing Activities at SLBN A Citeureup - Tiara Salshabilla Rafa; Ia Salsabila; Indah Auliya Muchtar; Nadia Syifa Azzahra; Shafira Indah Koeswardianie; Budi Susetyo; Iding Tarsidi (Jurnal Pendidikan Terapan, 2026)
Purpose: This study aims to examine the implementation of a smart iron as assistive technology to support visually impaired junior high school students in ironing activities at SLBN A Citeureup, particularly in improving independence, orientation and mobility, and daily living skills. Methods: This research employed a qualitative descriptive approach involving visually impaired junior high school students, skills teachers, and school staff at SLBN A Citeureup. Data were collected through observation, interviews, and documentation. The observations focused on students’ orientation and mobility development, social development, and independence during ironing activities using the smart iron. Data were analyzed through data reduction, data presentation, and conclusion drawing, while source and method triangulation were used to ensure data validity. Findings: The findings revealed that the implementation of the smart iron positively influenced students’ independence, confidence, and practical life skills. Students were able to recognize the parts and functions of the smart iron, follow audio instructions, distinguish temperatures through sound or vibration features, and iron clothes safely with minimal teacher assistance. In addition, the use of the smart iron improved students’ motor coordination, tactile abilities, social responsibility, and confidence in performing household activities independently. Teachers also confirmed that the voice guidance and automatic temperature features enhanced safety and reduced students’ dependence on assistance. Research Implications: The findings imply that assistive technology can play an important role in supporting inclusive education and daily living skills development for visually impaired students. The smart iron can be utilized as an adaptive learning medium to improve accessibility, safety, and independence in vocational and household activities. Originality: This study offers originality by specifically developing and implementing a smart iron with voice and sensor features as assistive technology for visually impaired students in ironing activities, an area that has received limited attention in previous studies.